Clinical, microbiological, immunological and metabolic features of purulent process occurrence in the periodontium in patients with chronic generalized periodontitis. - А. А. Gudaryan; N. B. Kuznyak; I. I. Dronik (Medičnì Perspektivi, 2016)
Significance of processes of freelipid peroxidation, local immunological disorders and features of biocenosis of periodontal tissues and their role in the occurrence of purulent process in the periodontium in 64 patients with chronic generalized periodontitis of I-II severity degree is proved. By total of results of clinical, microbiological and metabolic studies in patients it was showed, that formation of purulent process in periodontal tissues is due to the dominance in the gingival econiche of staphylococus, fuzospiliar infection, deficiency of secretory immunity of the oral mucosa, intensity of lipid peroxidation and inhibition of antioxidant protection. It was found that the normalization of the levels of immunoglobulins, especially of sIgA, cytokines (IL-1β, TNF-α), the operation of POL and AOP are the main markers of improved clinical picture of the disease.